2016
DOI: 10.1039/c6ra01772j
|View full text |Cite
|
Sign up to set email alerts
|

Porous gold nanoparticle/graphene oxide composite as efficient catalysts for reduction of 4-nitrophenol

Abstract: Porous gold nanoparticle/graphene oxide composites obtained through freeze-drying method show superior continuous catalytic performance in the reduction of 4-nitrophenol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…The diffraction pattern in Figure 4 curve b is in good agreement with face-centered cubic structure of metallic gold (JCPDS: 04-0784) [25,44].The peaks at 38.17, 44.28, 64.61and 77.72° are assigned to facecentered cubic bulk Au (111), (200), (220) and (311), respectively [45,46]. The crystallite size is calculated by Debye-Scherrer formula [47]: D = Kλ/βcosθ, where D is the particle size, K is the Scherrer constant (shape factor), λ is the wavelength of the X-ray, β is the full width half maximum (FWHM), θ is the Braggle angle.…”
Section: Xrd Measurementsupporting
confidence: 61%
“…The diffraction pattern in Figure 4 curve b is in good agreement with face-centered cubic structure of metallic gold (JCPDS: 04-0784) [25,44].The peaks at 38.17, 44.28, 64.61and 77.72° are assigned to facecentered cubic bulk Au (111), (200), (220) and (311), respectively [45,46]. The crystallite size is calculated by Debye-Scherrer formula [47]: D = Kλ/βcosθ, where D is the particle size, K is the Scherrer constant (shape factor), λ is the wavelength of the X-ray, β is the full width half maximum (FWHM), θ is the Braggle angle.…”
Section: Xrd Measurementsupporting
confidence: 61%
“…This phenomenon demonstrates the increasing of the disorder for the graphene carbon in the rGO/GNP sample, which could be ascribed to the breaking of graphene sheets into smaller pieces aer reduction. 35,37 The XPS spectra of rGO/GNP and GO samples clearly demonstrate the variation of the compositions. As shown in Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Then the glass sheet was put into a hydrothermal autoclave (50 mL) containing 1 mL of deionized water before heated at 180 C for 14 h. Aerwards, the formed hydrogel lm was freeze-dried under vacuum (À50 C) to obtain the resulting rGO/GNP aerogel lm (thickness $ 40 mm). 35 Finally, the lm was cut into pieces (2 mm  3 mm) and connected with a conductive copper paste (wrapped tightly with insulating tape to prevent the contact with the solution) to make the electrode for electrochemical measurements. The preparation process of aerogel lm and electrode is outlined in Scheme 1.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Au‐sponge with immobilized AuNPs showed even higher rate constant compared to systems with dispersed AuNPs and more than 100% more efficiency than any system with immobilized AuNPs. Recently, Zhang et al reported an Au/PEI/GO composite sponge with AuNPs immobilized on graphene oxide (GO) for catalyzing 4‐nitrophenol . The Au/PEI/GO composite sponge showed a very high K value of 9.87 × 10 −3 s −1 (= 0.5922 min −1 ), which was achieved on the base of high amount (0.68 mg, 13.6 wt%) of AuNPs in the sponges.…”
Section: Resultsmentioning
confidence: 99%
“…Ashby plot of the normalized rate constant ( K nor ) versus amount (mg) of Au on the supports. Au‐mSiO 2 dispersion,[24b] Au‐micelle dispersion,[6a] Au‐colloid dispersion,[24c] Au‐dendrimer dispersion, Au‐resin dispersion,[24a] Au‐collagen suspension, Au‐magnetic dispersion, Au‐ZnO paper, whiskers and powder, Au‐Si nanotube, Au‐boehmite films, Au‐PEI/PVA mats,[15e] and Au/PEI/GO …”
Section: Resultsmentioning
confidence: 99%